Bihermitian Structures On Complex Surfaces - Apostolov, Vestislav; Gauduchon, Paul; Grantcharov, Gueo (Proceedings of the London Mathematical Society, 2006)
We correct the statements of Theorem 1 and Corollary 2 of the above-mentioned paper and provide a new argument for Corollary 2. We also update some parts of the paper in the light of recent major developments in the theory of bihermitian structures, due to M. Gualtieri and N. Hitchin. 2000 Mathematics Subject Classification 53C26 (primary), 32J15, 53C56 (secondary).